A Temperature-Sensitive Misfolded bri1-301 Receptor Requires Its Kinase Activity to Promote Growth. Issue 4 (17th October 2018) - Zhang, Xiawei; Zhou, Linyao; Qin, Yukuo; Chen, Yongwu; Liu, Xiaolei; Wang, Muyang; Mao, Juan; Zhang, Jianjun; He, Zuhua; Liu, Linchuan; Li, Jianming
Abstract : bri1-301 is a temperature-sensitive misfolded brassinosteroid receptor that requires kinase activity to promote growth and is rapidly degraded in the endoplasmic reticulum and on the cell surface. Abstract: BRASSINOSTEROID-INSENSITIVE1 (BRI1) is a leucine-rich-repeat receptor-like kinase that functions as the cell surface receptor for brassinosteroids (BRs). Previous studies showed that BRI1 requires its kinase activity to transduce the extracellular BR signal into the nucleus. Among the many reported mutant bri1 alleles, bri1-301 is unique, as its glycine-989-to-isoleucine mutation completely inhibits its kinase activity in vitro but only gives rise to a weak dwarf phenotype compared with strong or null bri1 alleles, raising the question of whether kinase activity is essential for the biological function of BRI1. Here, we show that the Arabidopsis ( Arabidopsis thaliana ) bri1-301 mutant receptor exhibits weak BR-triggered phosphorylation in vivo and absolutely requires its kinase activity for the limited growth that occurs in the bri1-301 mutant. We also show that bri1-301 is a temperature-sensitive misfolded protein that is rapidly degraded in the endoplasmic reticulum and at the plasma membrane by yet unknown mechanisms. A temperature increase from 22°C to 29°C reduced the protein stability and biochemical activity of bri1-301, likely due to temperature-enhanced protein misfolding. The bri1-301 protein could be used as a model to study the degradation machinery for misfolded membrane proteins with cytosolic structural lesions and the plasma membrane-associated protein quality-control mechanism.